The Impact of Applying the Holonic Manufacturing System on Improving the Quality of Operational Performance in Industrial Organizations - Taher Hameed Abbas Bahia; Khawlah Radhi Athab (International Journal of Economics, Management and Accounting, 2025)
This study aims to enhance the quality of operational performance by implementing the Holonic Manufacturing System (HMS). The system involves dividing manufacturing processes into autonomous, collaborative, and participatory holons, including the Order Holon, Product Holon, Resource Holon, and Staff Holon. The primary objective is to optimize production efficiency by reducing costs, minimizing processing time, and increasing flexibility while improving overall organizational productivity. The research problem centers on evaluating the impact of holonic manufacturing on operational performance improvement. This study is significant as it addresses a critical issue for firms striving to enhance their efficiency and deliver value to customers. The adoption of HMS is not only a practical approach but also a widely recognized business strategy that has garnered interest from researchers and industry professionals alike.To achieve the study’s objectives, a structured questionnaire comprising 36 items was developed and distributed to participants. Two primary hypotheses were formulated to examine the relationship between HMS implementation and operational performance quality. Various statistical analyses were conducted using SPSS (version 24) and AMOS (version 24) to test the hypotheses and validate the findings. The results indicate a significant correlation and causal relationship between the Holonic Manufacturing System and operational performance quality. The findings suggest that implementing HMS effectively enhances organizational performance by improving production processes, increasing efficiency, and reducing operational constraints. Therefore, adopting this system can lead to a more agile, cost-effective, and productive manufacturing environment, making it a valuable strategy for modern organizations.